Transfer of workplace e-learning: A systematic literature review - Aidan O'Neill (Social Sciences and Humanities Open)
The paper describes a systematic review of literature published between January 2000 and October 2024 dealing with transfer of workplace e-learning. The review focused on theoretical frameworks, types of transfer being studied, and the types of transfer measurements employed to identify gaps in current knowledge and suggest directions for future research.Following a discussion of transfer of training, the paper discusses how e-learning differs from traditional face-to-face training. The factors differentiating workplace learning from learning in institutes of education are also explored, thereby establishing workplace e-learning, and its transfer, as a distinct area of study.The paper describes the search and filtering methodology used to identify relevant literature. The final corpus of thirty-one documents was studied to classify the type of transfer discussed in each document using six binary sub-categories of near and far transfer. In addition, transfer measurements were classified as self-reports, third-party reports, or objective measurements, and theoretical frameworks were recorded when the information was available. The information was examined to assess whether researchers used similar methodologies in approaching the topic of transfer of workplace e-learning.The results of the study show that there is not yet a broadly agreed approach for conducting research into transfer of workplace e-learning. There is no common scale or methodology used to describe and classify transfer, and the most common approach to measuring transfer is self-reports, which are subject to bias. These factors point to a need for further research to develop a robust academic framework for the subject, ideally supported by empirical research.